Microtentacle Actuators Based on Shape Memory Alloy Smart Soft Composite. (30th June 2020) - Lee, Hyun‐Taek; Seichepine, Florent; Yang, Guang‐Zhong
Abstract: Recent advances in miniature robotics have brought promising improvements in performance by leveraging the latest developments in soft materials, new fabrication schemes, and continuum actuation. Such devices can be used for applications that need delicate manipulation such as microsurgery or investigation of small‐scale biological samples. The shape memory effect of certain alloys is one of the promising actuation mechanisms at small scales because of its high work density and simple actuation mechanism. However, for sub‐millimeter devices, it is difficult to achieve complex and large displacement with shape memory alloy actuators because of the limitation in the fabrication process. Herein, a fabrication scheme for miniaturized smart soft composite actuator is proposed by utilizing two‐photon polymerization. The morphing modes are varied by changing the direction of the scaffold lamination. In addition, the actuation is controlled via local resistive heating of a carbon nanotube layer deposited inside of the actuators. The proposed design can generate a 390 µN force and achieve a bending angle up to 80°. Applications of the actuators are demonstrated by grasping small and delicate objects with single and two finger devices. Abstract : A novel fabrication process for the manufacturing of a miniaturized smart soft composite actuator is proposed. The soft microactuators are fabricated by embedding shape memory alloy wires in microscaffolds fabricated by a two‐photon polymerization process. Actuation characteristics of the actuators are evaluated, and microrobotic grippers composed of two actuators capable of grasping millimeter‐scale objects are proposed.